Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s13058-015-0549-4
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells mediate the clinical phenotype of inflammatory breast cancer in a preclinical model

Abstract: IntroductionInflammatory breast cancer (IBC) is an aggressive type of breast cancer, characterized by very rapid progression, enlargement of the breast, skin edema causing an orange peel appearance (peau d’orange), erythema, thickening, and dermal lymphatic invasion. It is characterized by E-cadherin overexpression in the primary and metastatic disease, but to date no robust molecular features that specifically identify IBC have been reported. Further, models that recapitulate all of these clinical findings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 38 publications
3
41
1
4
Order By: Relevance
“…the role of mesenchymal transitional cells in promoting E-cadherin (pivotal to IBC metastasis) expression in IBC cell models and metastases in xenografts [50, 75]. …”
Section: Discussionmentioning
confidence: 99%
“…the role of mesenchymal transitional cells in promoting E-cadherin (pivotal to IBC metastasis) expression in IBC cell models and metastases in xenografts [50, 75]. …”
Section: Discussionmentioning
confidence: 99%
“…This process is mediated by the activity of growth and transcription factors, leading to loss of the intercellular junction structure of epithelial cells, obtaining a mesenchymal morphology, loss of apical-basal cell polarity and migration/invasion capability [72][73][74]. Various investigations have also indicated that EMT is involved in cell plasticity, the process by which non-stem cells acquire stem cell characteristics [75][76][77]. The principal EMT molecular features include loss of the epithelial marker E-cadherin, and overexpression of mesenchymal markers N-cadherin and vimentin [78,79].…”
Section: Effect Of Melatonin In Epithelial Mesenchymal Transition Marmentioning
confidence: 99%
“…In a xenograft model, co-injection of MSCs with SUM149 inflammatory breast cancer cells increased skin invasion and metastasis in mice, mimicking clinical features of inflammatory breast cancer (IBC) (presenting as erythema and inflammation) compared with injection of SUM149 cells alone [47]. Compared with mice in which MSCs were not co-injected, primary tumors in mice with injected MSCs expressed higher phosphorylated EGFR levels and were associated with increased metastasis development after tumor resection, effects that were abrogated by treatment with the EGFR inhibitor erlotinib.…”
Section: Role Of the Egfr Pathway In The Progression Of Breast Cancermentioning
confidence: 99%